Do changes in socio-demographic characteristics impact up-to-date immunization status between 3 and 24 months of age? A prospective study among an inner-city birth cohort in the United States. Issue 5 (4th May 2017) - Pati, Susmita; Huang, Jiayu; Wong, Angie; Baba, Zeinab; Ostapenko, Svetlana; Fiks, Alexander G.; Cnaan, Avital
ABSTRACT: Introduction: Low-income child populations remain under-vaccinated. Our objective was to determine differences in the relative importance of maternal health literacy and socio-demographic characteristics that often change during early childhood on up-to-date (UTD) immunization status among a low-income population.Methods: We performed secondary data analysis of a longitudinal prospective cohort study of 744 Medicaid-eligible mother-infant dyads recruited at the time of the infant's birth from an inner-city hospital in the United States and surveyed every 6 months for 24 months. Our primary outcome was infant UTD status at 24 months abstracted from a citywide registry. We assessed maternal health literacy with the Test of Functional Health Literacy in Adults (short version). We collected socio-demographic information via surveys at birth and every 6 months. We compared predictors of UTD status at 3, 7, and 24 months.Results: The cohort consisted of primarily African-American (81.5%) mothers with adequate health literacy (73.9%). Immunizations were UTD among 56.7% of infants at 24 months of age. Maternal health literacy was not a significant predictor of UTD immunization status. Instead, adjusted results showed that significant predictors of not-UTD status at 24 months were lack of a consistent health care location or "medical home" (OR 0.17, 95%CI 0.18–0.37), inadequate prenatal care (OR 0.48, 95%CI 0.25–0.95), and prior not-UTD status (OR 0.31, 95%CI 0.20–0.47). Notably, all upper confidence limits are less than 1.0 for these variables. Health care location type (e.g., hospital-affiliate, community-based, none) was a significant predictor of vaccine status at age 3 months, 7 months, and 24 months.Conclusions: Investing in efforts to support early establishment of a medical home to obtain comprehensive coordinated preventive care, including providing recommended vaccines on schedule, is a prudent strategy to improve vaccination status at the population level.